Assessment of artificial substrates for evaluating groundwater microbial quality. (December 2016) - Voisin, Jérémy; Cournoyer, Benoit; Mermillod-Blondin, Florian
Highlights: Artificial substrates for monitoring bacterial groundwater quality were investigated. Biofilm growth indicators suggested clay beads and gravel particles to be more efficient for biofilm establishment than glass beads. Microbial diversity of different waters was well captured on clay beads and gravel particles. Clay beads were found to be the best artificial substrate for groundwater monitoring. Abstract: Protection of groundwater resources requires the development of reliable ecological indicators. Microorganisms involved in ecological services or being associated with particular hosts or habitats could be used for this purpose. Nevertheless, their tracking remains limited because of sampling issues, and a lack of devices for their long term monitoring. In the present study, three artificial substrates (glass and clay beads, and gravel particles) were tested in terms of efficacy at favoring bacterial growth, and at capturing bacterial diversity of waters (i.e., groundwater, surface water and wastewater). Total proteins, total carbohydrates, dehydrogenase and hydrolytic activities were used to monitor biofilm development on these artificial substrates. Fingerprinting analyses based on rrs (16S rRNA) − rrl (23S rRNA) spacer analyses (ARISA) and next generation sequencing (NGS) of partial rrs DNA segments (V5-V6) were used to compare operating taxonomic units (OTUs), and infer bacterial genera trapped on these substrates. Glass beads were found less efficient than the other two artificial substrates at increasing protein contents and microbial activities (hydrolytic and dehydrogenase activities). ARISA showed a discrimination of bacterial communities developing on artificial substrates that was matching water types. An incubation period of 7 days allowed a reliable assessment of bacterial diversity. From this incubation period, around 75% of water genera with more than four V5-V6 rrs DNA sequences detected in a water type were recovered from biofilms growing on artificial substrates. Based on relative abundances of genera, clay beads and gravel particles were more efficient than glass beads to capture and obtain bacterial communities matching those of the initial waters. Between 45–67% of similarities were found for these artificial substrates while it was between 36 and 43% for glass beads. This study demonstrated clay beads and gravel particles as being efficient tools for capturing bacterial diversity and monitoring bacterial growth. Overall, clay beads appeared the best choice for field monitoring because of the ease of their size standardization in comparison with gravel particles.